Psychological risk factors for a first hamstring strain injury in soccer: a qualitative study - Baize, D.; d`Arripe-Longueville, F.; Piponnier, E.; Scoffier-Meriaux, S. (Frontiers in Sports and Active Living, 2024)
Introduction: Hamstring strain injuries (HSIs) remain one of the most burdensome injuries in soccer. Current recommendations to prevent sports injuries suggest the importance for coaches and medical staff to consider psychological and contextual risk factors and to specify them according to the injury type and context. HSI risk factors in soccer have been widely investigated, mainly from physiological and biomechanical perspectives. However, psychological and health-related risk factors are still unexplored. Therefore, the objective of this study was to determine the psychological and health-related risk factors for a first HSI in male competitive soccer.